Animal monitoring based on IoT technologies (SHEEPIT) - Tavares, André Filipe Capelo (2018)
The weed control is characterized by being time consuming and needs to be carried out with frequency. In general, human, mechanical and chemical ways are the main mechanisms used to remove invasive species. As an alternative, animals are often used in this process, reducing the ecological / environmental footprint, since it excludes the use of any type of herbicide or artificial fertilizer. However, the addition of animals in the viticulture field creates threats to the fruit and challenges to companies responsible for the plantations maintenance. This work has the objective of developing a solution based on IoT technologies that allows monitoring and collecting physical and behavioral attributes. Among others, by providing activity and animal behavior, the system should create alarm patterns, information about relative geographical positioning, detection of sexual receptivity (e.g. estrous) or early identification of diseases.